Factors Affecting the Hydration Status of Foundry Workers - Permatasari, Vidya Jihan; Setyaningsih, Yuliani; Lestantyo, Daru (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Hydration status is a description of the conditions of workers when they lack fluid intake after work, one of which is due to the temperature of the workspace that exceeds the threshold value.This study aims to determine the effect of respondent characteristics and workspace temperature on hydration status in PT X metal foundry workers. This type of research is explanatory quantitative research with a cross sectional approach. The population in this study were PT X metal foundry workers, who were taken using purposive sampling technique, and obtained a sample of 69 people. Respondent data collection related to age, nutritional status, length of service, and volume of water intake using a questionnaire, workspace temperature data obtained through Questamp measurements, and hydration status data obtained through urine color tables. Data analysis included univariate analysis and bivariate analysis, using the spearman rank test and chi-square test. The results showed that the majority of workers were dehydrated. It was found that age, tenure, nutritional status, and heat had no correlation with hydration status. While between water intake and hydration status (p = 0.006) indicates that there is a relationship between the volume of water intake and hydration status, with the direction of the strength is not strong enough and a negative linear pattern. The conclusion obtained from this study is that there is an effect of hydration status on the volume of water intake with a negative correlation direction, while other independent variables are not related to the hydration status of metal foundry workers of PT X. Keywords: Heat Temperature, Hydration Status, Metal Casting